A comparative study of colour perception between designers and laypublic of constructed landmarks in Malaysian cities - Abdullah, Ahmad Saifuddin (2007)
The main purpose of the study is to explore the various schemes of colour perception or colour interpretation of the urban environment and to discover their potential part in interactions between the designers and the laypublic or users. It is also of equal importance to identify the differences and similarities in perception between the two respondent groups, and to develop possible ideological (based on or relating to a particular set of ideas or beliefs) presuppositions (when someone believes something is true without any proof) about the realities of urban design in relation to colours, especially in the context of the Malaysian cities. Such findings will facilitate a dialogue between decision-makers and users of the urban scene and enlarge possibilities for what can be called a common understanding and communicative action. This research will also deal with the perception of colour of the constructed landmarks between designers and laypublic and it is postulated that colour experience and the landmarks are mediated by the process of perception on the part of the individual. It will also study the aspect of familiarity and its influences on the judgement of constructed landmarks in six Malaysian cities. The study will adopt categories of constructed landmarks that include towers, buildings and special urban features such as bridges and stadium. The study will also be limited to identifying landmarks, investigating the significance of association with meanings and interpretation of colour (but not on the physics of colour), emotional response and physical evaluation based on surfacial values or visual appearance, familiarity, educational background and ethnicity which also formed the main variables. An exploratory survey will be conducted on the six selected cities namely Kuala Lumpur, Shah Alam, Johor Bahru, Pulau Pinang, Melaka, and Ipoh and former residents are the meant to be representative of a larger sampling group for the actual survey. The respondents are designers and the laypublic. The aim was to identify the landmarks for each city. The questionnaire will be open ended and this will allowed the respondents to express and answer the questions freely. The findings will be used to help in the design of the questionnaire for the pilot survey especially in identifying the range of responses derived from perception, colour perception and evaluation of the landmarks in selected Malaysian cities. The exercise is also meant to identify possible suitable candidates for the later part of the survey exercise.